Kavousi IIA : the late Minoan IIIC settlement at Vronda : the buildings on the summit - Day, Leslie Preston (Prehistory monographs, 2009)
Building A-B /Leslie Preston Day with contributions by Heidi Dierckx, David Reese, and Lynn Snyder --Building A --Periphery of building A --Building B --History and function of building A-B --Building P /Leslie Preston with contributions by Heidi Dierckx, David Reese, and Lynn Snyder --Building Q /Leslie Preston Day with contributions by Heidi Dierckx, David Reese, and Lynn Snyder --Building complex C-D /Nancy L. Klein with contributions by Heidi Dierckx [and others] --Building C --Building D --Periphery of building C-D --History and function of buildings C-D --Building complex J-K and building R /Lee Ann Turner with contributions by Heidi Dierckx [and others] --Building J --Building K --Building R --History and function of building complex J-K and building R --Appendix A : Kavousi coarse ware fabrics /Margaret S. Mook and Leslie Preston Day.